2018
DOI: 10.1016/j.supflu.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation and modelling of supercritical CO2 extraction process of carotenoids from carrot peels

Abstract: This work aimed to assess and optimise the extraction of carotenoids from carrot peels by supercritical CO2 (S-CO2), utilising ethanol as co-solvent. The evaluated variables were temperature, pressure and co-solvent concentration. According to the validated model, the optimal conditions for maximum mass yield (5.31%, d.b.) were found at 58.5 °C, 306 bar and 14.3% of ethanol, and at 59.0 °C, 349 bar and 15.5% ethanol for carotenoid recovery (86.1%). Kinetic experiments showed that 97% of the total extractable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(42 citation statements)
references
References 55 publications
1
38
0
3
Order By: Relevance
“…In food industry, carrots are used for the production of juice, jams, and in the preparation of ready to eat salads generating waste in the form of peels that accounts for around 11% of the initial weight. This industrial waste is a valuable source of carotenoids and can be sustainably extracted using green extraction techniques like supercritical CO 2 extraction [109]. In addition, about 25-35% of carrot harvest are discarded owed to irregular size, form or colour.…”
Section: Carrotmentioning
confidence: 99%
“…In food industry, carrots are used for the production of juice, jams, and in the preparation of ready to eat salads generating waste in the form of peels that accounts for around 11% of the initial weight. This industrial waste is a valuable source of carotenoids and can be sustainably extracted using green extraction techniques like supercritical CO 2 extraction [109]. In addition, about 25-35% of carrot harvest are discarded owed to irregular size, form or colour.…”
Section: Carrotmentioning
confidence: 99%
“…Some researchers reported lower yields in organic fertilizer treatments compared to mineral N fertilizer treatments (Chassy et al, 2006;Pieper and Barrett, 2009;Yu et al, 2010;Bilalis et al, 2018) due to nitrogen loss to the environment (Cheng et al, 2004), relatively lower initial plant available nitrogen, and slow organic nitrogen mineralization (Hartz et al, 2010). On the other hand, some studies have also found similar or higher yields when digestate was used as a fertilizer (Chantigny et al, 2008;Möller et al, 2008;Nkoa, 2014;de Andrade Lima et al, 2018). The distinct yield differences could be due to the variation in mineral nitrogen contents of the organic amendments and different organic matter mineralization rates.…”
Section: Tomato Yieldmentioning
confidence: 99%
“…With respect to the validated model, the optimal conditions for the maximum mass yield (5.31%) were found to be 58.5°C, 306 bar and 14.3% of ethanol, and to be 59°C, 349 bar and 15.5% ethanol for carotenoid recovery (86.1%). 35…”
Section: Supercritical Fluidsmentioning
confidence: 99%